From Jim crow to civil rights - Klarman, Michael J. (Oxford, 2004)
A monumental investigation of the Supreme Court's rulings on race, From Jim Crow To Civil Rights spells out in compelling detail the political and social context within which the Supreme Court Justices operate and the consequences of their decisions for American race relations.
Keywords: Segregation-Law and legislation-United states-History